Expectant management of abdominal pregnancy with good maternal and perinatal outcome - Charintip Somprasit (Chulalongkorn University, 2011)
Objective: To present a rare condition of ectopic pregnancy, abdominal pregnancy with good outcomes. Results: A 17 year-old primigravida at a gestational age of 31 weeks was diagnosed to have an abdominal pregnancy. She was successfully treated by expectant management until 33 weeks gestational age when delivery occurred via laparotomy with good maternal and perinatal outcome. After delivery of the fetus, the placenta was left in-situ. The patient recovered post-operatively and did not have additional complications. Conclusion: An advanced abdominal pregnancy can be managed expectantly at a tertiary care center.